Thermoplastics pipes and associated fittings for hot and cold water for domestic purposes and heating installations in buildings. Specification for chlorinated polyvinyl chloride (PVC-C) pipes and associated fittings and solvent cement Part 4, (31st May 1990) - British Standards Institution
No abstract available